Sosialisasi dan Edukasi Pemanfaatan Tanaman Berkhasiat Obat Dalam Menghadapi Masa Pandemi COVID-19 di Kota Kendari: Socialization and Education Of Effective Medicine Plants In Facing COVID-19 Pandemic in Kendari City - Andi Nafisah Tendri Adjeng; Ruslin Ruslin; La Ode Muhammad Fitrawan; Asniar Pascayantri (Jurnal Mandala Pengabdian Masyarakat, 2020)
Coronavirus-19 (COVID) has been declared as world pandemic by WHO. This virus is known to have originated in the city of Wuhan, China since December 2019. The President of the Republic of Indonesia has declared the status of this disease to be an Emergency Response stage in March 2020. In order to quickly handle COVID-19, public understanding of preventive measures for public health COVID-19 is needed in Indonesia, especially in several areas of Kendari City, namely Pondambea and Anduonohu villages. The aim of Halu Oleo University Internal Community Service (PKM) to the community was to help the local government increase public awareness to prevent and fight the Covid-19 virus in the form of utilizing nutritious plants that could increase the body's immune system. The form of community service activities was providing counseling, namely the door to door lecture and discussion method and the distribution of free leaflets and masks, the resulting output is an increase in community understanding and skills in cultivating and utilizing nutritious plants so as to achieve increased peace / public health (general public partners).